PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK MELALUI MEDIA POWERPOINT PADA TEMA 4 SUBTEMA 3 KELAS IV SD UMP - Dedy Irawan; Indah Nurlailasari; Arifin Muslim (Universitas Muhammadiyah Purwokerto, 2023)
The purpose of this research is to improve students learning achievement through powerpoint media in Class IV SD UMP. Problem solving with Classroom Action Research (CAR) with two cycles consisting of two meetings. Each cycle has stages starting from planning, action, observation and reflection referring to the Kemmis and Mc Taggart models. The data collection tool in this study used written test questions to measure student achievement. Based on the results of the study, it can be concluded that through powerpoint media, students learning achievement increases. The class average score increased from cycle I to cycle II, as well as the number of students who completed learning from cycle I to cycle II which increased.